Analisis Kegiatan Personal Selling Pada Produk Kopi 49 - Hafizh, Alif; Prasetio, Arie (eProceedings of Management, 2024)
Coffee consumption in Indonesia continues to increase, so this is directly proportional to coffee production whichcontinues to increase. Lampung Province is one of the largest contributors to coffee production in Indonesia,occupying the second place after South Sumatra Province. Kopi 49, which is in Lampung province, takes advantageof this booming business opportunity by producing processed coffee products, one of which is packaged coffee. Kopi49 is one of the packaged coffee SMEs in Bandar Lampung. Kopi 49 also uses a variety of integrated marketingcommunication activities to attract potential customers or distributors, one of which is using personal sellingmarketing communications. This study discusses the personal selling marketing communications carried out by Kopi49. The method used in this research is descriptive qualitative. Primary data collection techniques using interviews,observation and documentation. Secondary data collection techniques use online sources, literature and previousliterature. The data validation technique in this study uses source triangulation. The theory used in this study is 6Steps Personal selling by Kotler Keller (2016) which consists of Prospecting and qualifying, Preapproach,Presentation and demonstration, Overcoming objection, Closing, and Follow up and maintenance which formulatebasic principles which are key factors marketing strategy success. The results of this study can be concluded that Kopi49 has implemented every step contained in the theory Keywords-integrated marketing communication strategy, Coffee49, prospecting and qualifying, preapproach,presentation and demonstration, overcoming objection, closing, and follow up and maintenance